The Importance of Intercultural Communication to Improve Public Sector Leadership Competence - Gathmyr, Mohammad Raudy (Technium Social Sciences Journal, 2021)
This research is intended to answer the questions of how the ability of the political party cadres is to communicate across culture and what efforts should be made so that political party cadres have competence in intercultural communication. This is a qualitative research using a case study approach. Data collection was obtained from the results of semi-structured interviews with 6 informants consists of 4 public leaders from the district levels and 2 academicians. Informants were determined by purposive sampling which is aimed at making the data obtained more representative. The results of this study prove that intercultural communication competence is indispensable for political party cadres considering that they are potential leaders who will lead various regions in Indonesia with cultural diversity. The results of this study also prove that training related to intercultural communication for political party cadres is crucial and must be carried out by all political parties, not only at the central level but also at every branch office, because through this training, prospective leaders can improve the quality of their leadership.